Review of ultrasonic-based technology for oil film thickness measurement in lubrication. (January 2022) - Dou, Pan; Jia, Yaping; Zheng, Peng; Wu, Tonghai; Yu, Min; Reddyhoff, Tom; Peng, Zhongxiao
Abstract: Lubricant film thickness is the most informative variable that reflects lubrication conditions and transmission efficiency in the mechanical equipment, therefore its measurement is highly important. Despite a large number of theoretical models that have been developed to describe the lubricant film, complexities and uncertainties in a real tribo-pair contact still hinder the implementation of accurate and robust methods of in-situ film thickness measurements. Recently, ultrasonic-based measurement has been widely studied, showing promising potential owing to its non-destructive characteristics, high sensitivity, and limited physical modifications. This paper comprehensively reviews basic principles of ultrasonic-based oil film measurement; summarizes progress on calculation models and associated signal processing methods; exhibits in-lab demonstrations and in-situ applications; and discusses key technical issues and possible solutions.